Patient, Family, and Health Professional Perspectives of How Families are Involved in Adult Inpatient Traumatic Brain Injury Rehabilitation - Kaylee Eady; Katherine Moreau; Shawn Marshall; Mary Egan (Patient Experience Journal)
Objective: We aimed to answer the following research question: From the perspectives of patients, family members, and health professionals, how are families involved in the rehabilitation of adult patients with Traumatic Brain Injury at an inpatient Acquired Brain Injury service within an adult rehabilitation centre? Methods: We used an interpretive qualitative approach, from a constructivist view. This approach allowed us to understand and describe family involvement from the perspectives of patients with Traumatic Brain Injury, family members, and health professionals. We conducted one-on-one interviews with patients, family members, and health professionals. We used a three-step analysis method: data reduction, data display, and conclusions/verifications. Results: Six patients, four family members, and ten health professionals participated. Participants described how families are involved in supporting and encouraging the patient, seeking and exchanging information, making decisions, and care and therapy. Conclusion: Overall, patients and family members perceived family involvement as critical, while health professionals viewed it as not always necessary. This study also revealed that patients and family members shared similar understandings of family involvement but had different understandings than health professionals. Recognizing that the adult population and rehabilitation processes are unique and complex, we need to understand how to support family involvement, through patient- and family-centered care, in this type of setting. We also need to understand how to better facilitate patient-family-health professional collaboration.